2022
DOI: 10.1111/jbi.14460
|View full text |Cite
|
Sign up to set email alerts
|

Regional and local environment drive biogeographic patterns in intertidal microorganisms

Abstract: Aim: Understanding large-scale spatial distribution patterns is not only a central goal of ecology but is also essential for conservation planning. Nevertheless, the biogeographical patterns of diversity and composition remain unclear for microorganisms and the role of various factors in structuring their assemblages is still poorly known.Here, we tested whether the diversity and community structure of ciliates are driven by both local environmental and regional dispersal-related processes.Location: Coasts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
(87 reference statements)
3
6
0
Order By: Relevance
“…One explanation is that bacterial communities are filtered by large-scale environmental conditions. Similar findings were reported by Xu et al (2022) that benthic ciliate communities along the coast of China were driven by large-scale environmental filtering related to the outflow of the Yangtze River. Another possible explanation may be the prevalence of generalist bacteria, which can adapt to a wide range of conditions (Székely and Langenheder 2014).…”
Section: Assembly Processes Governing Bacterial Communities Across Sp...supporting
confidence: 90%
See 2 more Smart Citations
“…One explanation is that bacterial communities are filtered by large-scale environmental conditions. Similar findings were reported by Xu et al (2022) that benthic ciliate communities along the coast of China were driven by large-scale environmental filtering related to the outflow of the Yangtze River. Another possible explanation may be the prevalence of generalist bacteria, which can adapt to a wide range of conditions (Székely and Langenheder 2014).…”
Section: Assembly Processes Governing Bacterial Communities Across Sp...supporting
confidence: 90%
“…1a): high‐latitude region (latitude > 35°N; hereafter REG_H), middle‐latitude region (35°N > latitude > 25°N; hereafter REG_M) and low‐latitude region (latitude < 25°N; hereafter REG_L). This separation generally corresponds to the three ecoregions suggested by former studies (Spalding et al 2007, Xu et al 2022). Sampling sites (1 m 2 ) were in the mid‐tidal zone at 100 m intervals, and the number of sites per beach (6–18) was proportional to the length of the beach (Fig.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Soil bacterial α‐diversity is known to be governed by both species pool and local community assembly mechanisms (Xu et al., 2022). Moreover, the effects of species pools and local assembly processes will vary dramatically between saturated and unsaturated communities.…”
Section: Discussionmentioning
confidence: 99%
“…The marine ecoregion is a global bioregionalization of coastal and shelf areas and is used widely in macroorganisms [25]. Recent studies on sedimental archaea and ciliates, and planktonic microeukaryotes also showed that the biogeographical patterns of microorganisms, similar to macroorganisms, correspond well with the ecoregional delineations [26,55,57]. Our findings confirmed that the clustering of communities was primarily driven by the habitat types (e.g., water vs. sediment) and, within each habitat type, there were notable regional effects (e.g., ecoregions) [58].…”
Section: Similar Biogeographical Patterns With Distinct Assembly Mech...mentioning
confidence: 99%